Video-Assisted Thoracoscopic versus Robotic-Assisted Thoracoscopic Thymectomy: Systematic Review and Meta-analysis. Issue 4 (July 2017) - Fok, Matthew; Bashir, Mohamad; Harky, Amer; Sladden, David; DiMartino, Mariano; Elsyed, Hazim; Howard, Callum; Knipe, Maxwell; Shackcloth, Michael J.
Objective: Minimally invasive thoracic surgical procedures, performed with or without the assistance of a robot, have gained popularity over the last decade. They have increasingly become the choice of intervention for a number of thoracic surgical operations. Minimally invasive surgery decreases postoperative pain, hospital stay and leads to a faster recovery in comparison with conventional open methods. Minimally invasive techniques to perform a thymectomy include video-assisted thoracoscopic surgery (VATS) or robotic-assisted thoracoscopic surgery (RATS). In this study, we aim to systematically review and interrogate the literature on minimally invasive thymectomy and draw a meta-analysis on the outcomes between the two approaches. Methods: An extensive electronic health database search was performed on all articles published from inception to May 2015 for studies describing outcomes in VATS and RATS thymectomy. Results: A total of 350 patients were included in this study, for which 182 and 168 patients underwent RATS and VATS thymectomy, respectively. There were no recorded in-hospital deaths for either procedure. There was no statistical difference in conversion to open, length of hospital stay, or postoperative pneumonia. Operational times for RATS thymectomy were longer. Conclusions: The VATS and RATS thymectomy offer good and safe operative and perioperative outcomes. There is little difference between the two groups. However, there is poor evidence basis for the long-term outcomes in minimally invasive procedures for thymectomy. It is imperative that future studies evaluate oncological outcomes both short and long term as well as those related to safety.